A review of mechanical deformation and seepage mechanism of rock with filled joints - Lei Yue; Wei Li; Yu Liu; Shuncai Li; Jintao Wang (Deep Underground Science and Engineering)
Abstract Various defects exist in natural rock masses, with filled joints being a vital factor complicating both the mechanical characteristics and seepage mechanisms of the rock mass. Filled jointed rocks usually show mechanical properties that are weaker than those of intact rocks but stronger than those of rocks with fractures. The shape of the rock, filling material, prefabricated fissure geometry, fissure roughness, fissure inclination angle, and other factors mainly influence the mechanical and seepage properties. This paper systematically reviews the research progress and findings on filled rock joints, focusing on three key aspects: mechanical properties, seepage properties, and flow properties under mechanical response. First, the study emphasizes the effects of prefabricated defects (shape, size, filling material, inclination angle, and other factors) on the mechanical properties of the rock. The fracture extension behavior of rock masses is revealed by the stress state of rocks with filled joints under uniaxial compression, using advanced auxiliary test techniques. Second, the seepage properties of rocks with filled joints are discussed and summarized through theoretical analysis, experimental research, and numerical simulations, focusing on organizing the seepage equations of these rocks. The study also considers the form of failure under stress–seepage coupling for both fully filled and partially filled fissured rocks. Finally, the limitations in the current research on the rock with filled joints are pointed out. It is emphasized that the specimens should more closely resemble real conditions, the analysis of mechanical indexes should be multi‐parameterized, the construction of the seepage model should be refined, and the engineering coupling application should be multi‐field–multiphase.